IMF Research Bulletin, June 2011. (IMF Research Bulletin; IMF Research Bulletin ;, 2001)
June 2011: The Q and A in this issue features seven questions on the global trade collapse of 2008-09 (by Rudolfs Bems); the research summaries are "The Impact of the Great Recession on Emerging Markets" (by Ricardo Llaudes, Ferhan Salman, and Mali Chivakul) and "The Missing Link between Dutch Disease, Appreciation, and Growth (by Nicolas E. Magud and Sebastian Sosa). The issue also lists the contents of the June 2011 issue of the IMF Economic Review, Volume 59 Number 2; visiting scholars at the IMF during April-June 2011; and recent IMF Working Papers and Staff Discussion Notes.